Reinventing education : beyond the knowledge economy - Watkins, Alan, 1961-; Silver, Matt (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"The need for change in the education system is obvious and overwhelming. But each stakeholder group has their own ideas about why the system is broken and how to fix it. Competing priorities, political inertia and diminishing budgets maintain the dysfunctional status quo. This essential text examines the underlying causes behind the key challenges facing schools, and argues that we need to move from knowledge transfer systems to a deliberately developmental approach that transforms capabilities including emotional regulation, systems thinking, critical analysis, creativity, and collaborative capability. The chapters provide a framework for designing, constructing and implementing school systems that can transform the outcome in a classroom, school or trust. Topics covered include: Why education is a 'wicked' problem Why development must be central and sit alongside knowledge transfer (as AI takes over 'expertise') How motivation and value systems evolve and are key to change How to drive behaviour change to transform outcomes What human-centred means now in a reinvented system Offering much-needed insights, guidance and solutions for teachers, school leaders and policy-makers, this book will be valuable reading for all those interested in school improvement and education policy"-- Provided by publisher.
Current reality in education -- Glimmers of change -- Awareness before change -- Individual development in theory -- Individual development in practise -- Individual development in action -- Collective development in theory -- Collective development in practice -- Collective development in action -- Behaviour & systems development in theory -- Behaviour & systems development in practice -- Behaviour & systems development in action -- TKAT case study.
Includes bibliographical references and index.
Keywords: Educational change -- Great Britain; Education -- Aims and objectives -- Great Britain